Non-crosslinked polyethylene material and preparation method thereof
By using polyethylene, phosphorus-based flame retardant and modified polyhedral oligosilsesquioxane and its derivative flame retardant synergistic agent, the problem of poor flame retardant and dielectric properties of existing materials is solved, and the efficient flame retardant and excellent dielectric properties of the materials are achieved.
Patent Information
- Application Number
- CN202411993299.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The flame retardant and dielectric properties of existing non-crosslinked polyethylene materials are poor, making it difficult to meet the safety and performance requirements in actual applications.
Polyethylene, phosphorus-based flame retardant, modified polyhedral oligosilsesquioxane and its derivative flame retardant synergistic agent are used as raw materials to prepare non-crosslinked polyethylene materials through intensive refining and extrusion granulation processes. The modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist contain boron elements, an annular structure with a carbon-hydrogen ratio greater than 1, and an inorganic silicone cage core, which can form a carbon layer, a ceramic barrier layer and a protective film during the combustion process, significantly improving the flame retardant performance of the material.
It significantly improves the flame retardant performance and dielectric properties of non-crosslinked polyethylene materials, can reach the V0 flame retardant grade, and has excellent oxygen index and relative dielectric constant, enhancing the safety and performance of the material.
Smart Images

Figure CN119752016A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a non-cross-linked polyethylene material. Background Art
[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0003] Ordinary polyethylene sheath materials are generally composed of several polyethylene resins, antioxidants, lubricants and carbon black in a certain proportion, and then made by twin-screw extrusion granulation. They have high tensile strength and elongation at break, good extrusion fluidity, and a wide range of processing temperatures. However, there is an obvious disadvantage - no flame retardancy. For flame retardants with high polarity, such as nitrogen-based flame retardants, such as melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, melamine, etc., the dielectric constant of polyethylene will be greatly affected. The magnesium-aluminum flame retardant has a good flame retardant performance when the filling degree reaches more than 60%, and the increase in the amount added will also increase the dielectric constant of polyethylene. Therefore, it is very necessary to develop a non-cross-linked polyethylene material with good flame retardancy and dielectric properties. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a non-cross-linked polyethylene material, aiming to solve the problem of poor flame retardancy and dielectric properties of the current non-cross-linked polyethylene material.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a non-cross-linked polyethylene material, wherein the raw materials of the non-cross-linked polyethylene material, measured in parts by weight, include:
[0007] Polyethylene 50-90 parts,
[0008] Phosphorus flame retardant 10-20 parts,
[0009] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0010] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0011]
[0012] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0013] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0014] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;
[0015] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
[0016] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0017]
[0018] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.
[0019] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:
[0020] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;
[0021] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0022] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0023] In some embodiments of the present invention, the polyethylene includes at least one of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, and high-density polyethylene;
[0024] And / or, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphorus oxide. ,
[0025] In some embodiments of the present invention, the raw material of the non-cross-linked polyethylene material further includes at least one of a toughening agent and a compatibilizer. The raw material is calculated in parts by weight, and the toughening agent is 5-10 parts, and the compatibilizer is 3-8 parts. ,
[0026] In some embodiments of the present invention, the toughening agent includes at least one of ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer.
[0027] In some embodiments of the present invention, the raw materials of the non-cross-linked polyethylene material also include at least one of a lubricant, an antioxidant, and carbon black; wherein, the raw materials are calculated by weight, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, and the carbon black is 5-6 parts.
[0028] In a second aspect, the present invention provides a method for preparing the above-mentioned non-cross-linked polyethylene material, comprising the following steps:
[0029] The raw materials, including polyethylene, phosphorus-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight portions to obtain an internal mixer material;
[0030] The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the non-cross-linked polyethylene material.
[0031] In some embodiments of the present invention, the raw material further comprises at least one of a lubricant, an antioxidant, and carbon black;
[0032] And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 150°C-180°C;
[0033] And / or, the drying temperature is 80°C-90°C.
[0034] The non-crosslinked polyethylene material of the invention comprises polyethylene, a phosphorus-based flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant, dielectric and mechanical properties of the non-cross-linked polyethylene material. The non-cross-linked polyethylene material provided by the present invention has good flame retardant and dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;
[0036] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0038] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0039] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0040] Ordinary polyethylene sheath materials are generally composed of several polyethylene resins, antioxidants, lubricants and carbon black in a certain proportion, and then made by twin-screw extrusion granulation. They have high tensile strength and elongation at break, good extrusion fluidity, and a wide range of processing temperatures. However, there is an obvious disadvantage - no flame retardancy. For flame retardants with high polarity, such as nitrogen-based flame retardants, such as melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, melamine, etc., the dielectric constant of polyethylene will be greatly affected. The magnesium-aluminum flame retardant has a good flame retardant performance when the filling degree reaches more than 60%, and the increase in the amount added will also increase the dielectric constant of polyethylene. Therefore, it is very necessary to develop a non-cross-linked polyethylene material with good flame retardancy and dielectric properties.
[0041] In order to solve the above problems, the first aspect of the present invention provides a non-cross-linked polyethylene material. The raw materials of the non-cross-linked polyethylene material, measured by weight, include:
[0042] 35-55 parts of ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer,
[0043] Polyethylene 50-90 parts,
[0044] Phosphorus flame retardant 10-20 parts,
[0045] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0046] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0047]
[0048] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0049] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0050] It can be understood that the polyethylene is any number between 50-90 parts, such as 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, etc.; the phosphorus-based flame retardant is any number between 10-20 parts, such as 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.; the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any number between 2-8 parts, such as 2 parts, 4 parts, 6 parts, 8 parts, etc.
[0051] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.
[0052] It is understandable that phosphorus-based flame retardants decompose to form a non-flammable liquid film of phosphoric acid during combustion. At the same time, phosphoric acid is further dehydrated to form metaphosphoric acid, which is further polymerized to form polymetaphosphoric acid. In this process, not only does the covering layer generated by phosphoric acid have a covering effect, but also because the generated polymetaphosphoric acid is a strong acid and a strong dehydrating agent, it dehydrates the polymer and carbonizes it, changing the mode of the polymer combustion process and forming a carbon film on its surface to isolate the air, thereby exerting a stronger flame retardant effect. At the same time, phosphorus-based flame retardants are also a free radical scavenger. Using mass spectrometry technology, it is found that any phosphorus-containing compound forms PO· when the polymer burns. It can combine with hydrogen atoms in the flame area to suppress the flame. In addition, the moisture produced by phosphorus flame retardants during the flame retardant process can reduce the temperature of the condensed phase on the one hand, and dilute the concentration of combustibles in the gas phase on the other hand. The B in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons, and can produce a synergistic effect when coordinated with phosphorus, thereby improving the flame retardant effect. In addition, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, isolating the release of combustible gases and the entry of external heat into the interior; hydrocarbons The ring structure R2 with a ratio greater than 1 has a higher carbon-hydrogen ratio. The benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent heat transfer, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process. The anti-drip effect is greatly improved. At the same time, it isolates heat and oxygen transfer and reduces the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contains a large amount of silicon and oxygen elements. During the combustion of the polymer, it forms phosphates with the acidic gas after the combustion of the phosphorus flame retardant, which promotes the reaction between the phosphorus element and the polymer, thereby quickly forming a carbon layer. The SiO generated after the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant 2 Interspersed in the coke layer, it acts like sand in cement, making the coke layer more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material. The boron in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons and can produce a synergistic effect when coordinated with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster.
[0053] The non-crosslinked polyethylene material of the invention comprises polyethylene, a phosphorus-based flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant and dielectric properties of the non-cross-linked polyethylene material. The non-cross-linked polyethylene material provided by the present invention has excellent flame retardant and dielectric properties.
[0054] In some embodiments, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
[0055] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.
[0056] In some embodiments, R2 is a benzofuranyl group.
[0057] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.
[0058] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.
[0059] In some embodiments, R2 is a naphthyl ring group.
[0060] In some embodiments, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0061]
[0062] In some embodiments, the molar ratio of compound 1 to compound 2 during the above reaction is 2:1.
[0063] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.
[0064] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.
[0065] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.
[0066] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.
[0067] In some embodiments, compound 2 is dibenzofuran-3-boronic acid.
[0068] In some embodiments, the structural formula of compound 3 is:
[0069]
[0070] The following is designated as modified POSS flame retardant synergist 1.
[0071] In some embodiments, the structural formula of compound 3 is:
[0072]
[0073] The following is designated as modified POSS flame retardant synergist 2.
[0074] In some embodiments, the preparation method of compound 3 comprises the following steps:
[0075] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;
[0076] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0077] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0078] In some embodiments, the catalyst is acetic acid.
[0079] In some embodiments, the solvent is ethanol.
[0080] In some embodiments, the raw material of the non-cross-linked polyethylene material further comprises polyethylene, and the polyethylene accounts for 5-10 parts by weight.
[0081] In some embodiments, the polyethylene includes at least one of low density polyethylene, linear low density polyethylene, medium density polyethylene, and high density polyethylene.
[0082] In some embodiments, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide flame retardant;
[0083] It is understood that the phosphorus-based flame retardants include, but are not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum hypophosphite, methylethyl aluminum hypophosphite and phenyl aluminum hypophosphite.
[0084] In some embodiments, the phosphorus-based flame retardant is diethyl aluminum phosphite.
[0085] In some embodiments, the nitrogen-based flame retardant is melamine urate.
[0086] In some embodiments, the raw material of the non-cross-linked polyethylene material further includes at least one of a toughening agent and a compatibilizer. The raw material is calculated in parts by weight, wherein the toughening agent is 5-10 parts and the compatibilizer is 3-8 parts.
[0087] In some embodiments, the toughening agent includes at least one of ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer.
[0088] It can be understood that the addition of toughening agent can further improve the mechanical properties of polyethylene.
[0089] In some embodiments, the compatibilizer is a maleic anhydride grafted compatibilizer, including but not limited to PE grafted maleic anhydride (PE-g-MAH), POE grafted maleic anhydride (POE-g-MAH) and EMA grafted maleic anhydride (EMA-g-MAH). The above compatibilizer enhances the polarity and reactivity of the base material by grafting maleic anhydride (MAH), a polar monomer, onto polyethylene (PE), polyolefin elastomer (POE) and ethylene-maleic anhydride copolymer (EMA), thereby improving their compatibility with other polar materials to improve the performance of the product in all aspects.
[0090] In some embodiments, the raw material of the non-cross-linked polyethylene material also includes at least one of a lubricant, an antioxidant, and carbon black; wherein, the raw materials are calculated by weight, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, and the carbon black is 5-6 parts.
[0091] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding a lubricant, it is beneficial to promote the mixing of various raw materials to be more uniform, while improving the fluidity of the polymer resin, reducing the friction coefficient, making the surface of the product smoother, improving processing efficiency, and improving the transparency and gloss of the plastic. The type of lubricant is not limited here, and those skilled in the art can select it according to actual needs.
[0092] In some embodiments, the antioxidant includes but is not limited to asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants. Hindered phenol antioxidants include but are not limited to antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), BHT (2,6-di-tert-butyl-p-cresol), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate); aromatic amine antioxidants include but are not limited to diphenylamine, p-phenylenediamine and dihydroquinoline and its derivatives or polymers, such as antioxidant 445 (4,4'-bis(α.α- The antioxidants include, but are not limited to, dimethylbenzyl)diphenylamine); thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearate thiodipropionate), and DSTP (octadecyl thiodipropionate); phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol diphosphite distearyl), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite). By adding antioxidants, the antioxidant properties and aging resistance of polymer materials are beneficial, and the service life of polymer materials is extended. The types of antioxidants are not limited here, and those skilled in the art can choose according to actual needs.
[0093] In a second aspect, the present invention provides a method for preparing the above-mentioned non-cross-linked polyethylene material, comprising the following steps:
[0094] The raw materials, including polyethylene, phosphorus-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight portions to obtain an internal mixer material;
[0095] The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the non-cross-linked polyethylene material.
[0096] In some embodiments, the raw material further comprises at least one of a lubricant, an antioxidant, and carbon black;
[0097] And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 150°C-180°C;
[0098] And / or, the drying temperature is 80°C-90°C.
[0099] The content of the present invention is explained below through specific examples and data. The information of the raw materials involved in the specific implementation method is shown in Table 1:
[0100] Table 1 Information of raw materials of Examples and Comparative Examples
[0101]
[0102]
[0103] Preparation method of modified POSS flame retardant synergist 1
[0104] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 1.
[0105] Preparation method of modified POSS flame retardant synergist 2
[0106] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain dibenzofuran-3-boric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 2.
[0107] Preparation method of modified POSS flame retardant synergist 3
[0108] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain methylboric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 3.
[0109] Preparation method of modified POSS flame retardant synergist 4
[0110] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain phenylboronic acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 4.
[0111] Embodiment 1:
[0112] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0113] LLDPE 50 parts;
[0114] 20 parts of diethyl aluminum hypophosphite;
[0115] 18 parts of modified POSS flame retardant synergist;
[0116] PE wax 0.5 parts;
[0117] Antioxidant 10100.5 parts;
[0118] 5 parts of carbon black;
[0119] The preparation method is:
[0120] Mixing raw materials, including LLDPE, diethyl aluminum hypophosphite modified POSS flame retardant synergist 1, PE wax, antioxidant 1010, and carbon black, in an internal mixer according to weight parts to obtain an internal mixer material;
[0121] The mixed material is extruded and granulated at 150°C-180°C by a twin-screw extruder with a length-to-diameter ratio of (35-40):1 to obtain a granular material;
[0122] The granules are dried at 80°C-90°C to obtain a non-crosslinked polyethylene material.
[0123] Embodiment 2:
[0124] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0125] LLDPE 90 parts;
[0126] 15 parts of diethyl aluminum hypophosphite;
[0127] 15 parts of modified POSS flame retardant synergist;
[0128] PE wax 0.5 parts;
[0129] Antioxidant 10100.5 parts;
[0130] 5 parts of carbon black;
[0131] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0132] Embodiment 3:
[0133] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0134] LLDPE 70 parts;
[0135] 10 parts of diethyl aluminum hypophosphite;
[0136] 12 parts of modified POSS flame retardant synergist;
[0137] PE wax 0.5 parts;
[0138] Antioxidant 10100.5 parts;
[0139] 5 parts of carbon black;
[0140] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0141] Embodiment 4:
[0142] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0143] LLDPE 70 parts;
[0144] 15 parts of diethyl aluminum hypophosphite;
[0145] 15 parts of modified POSS flame retardant synergist;
[0146] PE wax 0.5 parts;
[0147] Antioxidant 10100.5 parts;
[0148] 5 parts of carbon black;
[0149] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0150] Embodiment 5:
[0151] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0152] LLDPE 70 parts;
[0153] 5 parts of octacarbon POE;
[0154] 15 parts of diethyl aluminum hypophosphite;
[0155] 15 parts of modified POSS flame retardant synergist;
[0156] PE-g-MAH 8 parts;
[0157] PE wax 0.5 parts;
[0158] Antioxidant 10100.5 parts;
[0159] 5 parts of carbon black;
[0160] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0161] Embodiment 6:
[0162] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0163] LLDPE 70 parts;
[0164] 10 parts of octacarbon POE;
[0165] 15 parts of diethyl aluminum hypophosphite;
[0166] 15 parts of modified POSS flame retardant synergist;
[0167] PE-g-MAH 3 parts;
[0168] PE wax 0.5 parts;
[0169] Antioxidant 10100.5 parts;
[0170] 5 parts of carbon black;
[0171] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0172] Embodiment 7:
[0173] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0174] MDPE 70 parts;
[0175] 15 parts of diethyl aluminum hypophosphite;
[0176] 15 parts of modified POSS flame retardant synergist;
[0177] PE wax 0.5 parts;
[0178] Antioxidant 10100.5 parts;
[0179] 5 parts of carbon black;
[0180] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0181] Embodiment 8:
[0182] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0183] LLDPE 70 parts;
[0184] 15 parts of diethyl aluminum hypophosphite;
[0185] 25 parts of modified POSS flame retardant synergist;
[0186] PE wax 0.5 parts;
[0187] Antioxidant 10100.5 parts;
[0188] 5 parts of carbon black;
[0189] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0190] Embodiment 9:
[0191] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0192] LLDPE 35 parts;
[0193] MDPE 35 parts;
[0194] 15 parts of diethyl aluminum hypophosphite;
[0195] 15 parts of modified POSS flame retardant synergist;
[0196] PE wax 0.5 parts;
[0197] Antioxidant 10100.5 parts;
[0198] 5 parts of carbon black;
[0199] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0200] Embodiment 10:
[0201] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0202] LLDPE 70 parts;
[0203] 15 parts of diethyl aluminum hypophosphite;
[0204] 15 parts of modified POSS flame retardant synergist;
[0205] PE wax 0.2 parts;
[0206] 10102 parts of antioxidant;
[0207] 6 parts of carbon black;
[0208] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0209] Embodiment 11:
[0210] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0211] LLDPE 70 parts;
[0212] 15 parts of diethyl aluminum hypophosphite;
[0213] 15 parts of modified POSS flame retardant synergist;
[0214] 1 part of PE wax;
[0215] Antioxidant 10101.2 parts;
[0216] Carbon black 5.5 parts;
[0217] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0218] Comparative Example 1:
[0219] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0220] LLDPE 70 parts;
[0221] 8 parts of diethyl aluminum hypophosphite;
[0222] 112 parts of modified POSS flame retardant synergist;
[0223] PE wax 0.5 parts;
[0224] Antioxidant 10100.5 parts;
[0225] 5 parts of carbon black;
[0226] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0227] Comparative Example 2:
[0228] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0229] LLDPE 70 parts;
[0230] 20 parts of diethyl aluminum hypophosphite;
[0231] PE wax 0.5 parts;
[0232] Antioxidant 10100.5 parts;
[0233] 5 parts of carbon black;
[0234] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0235] Comparative Example 3:
[0236] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0237] LLDPE 70 parts;
[0238] 120 parts of modified POSS flame retardant synergist;
[0239] PE wax 0.5 parts;
[0240] Antioxidant 10100.5 parts;
[0241] 5 parts of carbon black;
[0242] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0243] Comparative Example 4:
[0244] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0245] LLDPE 70 parts;
[0246] MAC 15 copies;
[0247] 15 parts of modified POSS flame retardant synergist;
[0248] PE wax 0.5 parts;
[0249] Antioxidant 10100.5 parts;
[0250] 5 parts of carbon black;
[0251] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0252] Comparative Example 5:
[0253] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0254] LLDPE 70 parts;
[0255] 15 parts of diethyl aluminum hypophosphite;
[0256] 5 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;
[0257] PE wax 0.5 parts;
[0258] Antioxidant 10100.5 parts;
[0259] 5 parts of carbon black;
[0260] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0261] Comparative Example 6:
[0262] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0263] LLDPE 70 parts;
[0264] 15 parts of diethyl aluminum hypophosphite;
[0265] 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;
[0266] PE wax 0.5 parts;
[0267] Antioxidant 10100.5 parts;
[0268] 5 parts of carbon black;
[0269] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0270] Comparative Example 7:
[0271] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0272] LLDPE 70 parts;
[0273] 15 parts of diethyl aluminum hypophosphite;
[0274] 1.6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;
[0275] 3.4 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;
[0276] PE wax 0.5 parts;
[0277] Antioxidant 10100.5 parts;
[0278] 5 parts of carbon black;
[0279] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0280] Comparative Example 8:
[0281] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0282] LLDPE 70 parts;
[0283] 15 parts of diethyl aluminum hypophosphite;
[0284] 35 parts of modified POSS flame retardant synergist;
[0285] PE wax 0.5 parts;
[0286] Antioxidant 10100.5 parts;
[0287] 5 parts of carbon black;
[0288] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0289] Comparative Example 9:
[0290] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0291] LLDPE 70 parts;
[0292] 15 parts of diethyl aluminum hypophosphite;
[0293] 45 parts of modified POSS flame retardant synergist;
[0294] PE wax 0.5 parts;
[0295] Antioxidant 10100.5 parts;
[0296] 5 parts of carbon black;
[0297] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.
[0298] The non-cross-linked polyethylene materials obtained in the above examples and comparative examples were injection molded or pressed into sheets, and tested for flame retardancy, oxygen index, relative dielectric constant, tensile strength, and elongation at break. The test standards were as follows:
[0299] (1) Flame retardant grade
[0300] The test was conducted according to the UL94 standard, with a sample thickness of 3 mm and a test temperature of 23 ± 2 ° C. Three samples were tested using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd., and any dripping was observed.
[0301] (2) Oxygen index
[0302] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The oxygen index of three samples is tested using the oxygen index tester device of Fangshang Analytical Instrument Equipment Factory, Jiangning District, Nanjing, and the results are averaged.
[0303] (3) Relative dielectric constant
[0304] The test was conducted according to Method A of GB / T 1693-2007. The relative dielectric constants of three samples were tested using the dielectric constant experimental device of Nanjing Huicheng Instrument Co., Ltd., and the results were averaged.
[0305] (4) Tensile strength and elongation at break
[0306] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of three specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.
[0307] The test results are shown in Table 3.
[0308] Table 2 Examples of the present invention and comparative examples
[0309]
[0310]
[0311]
[0312]
[0313]
[0314] Table 3 Performance test table of the embodiments of the present invention and comparative examples
[0315]
[0316] According to Table 3, it can be seen that the flame retardant properties of the non-crosslinked polyethylene injection molded sheets of Examples 1-11 are good, the flame retardant grades all reach the V0 level, no dripping occurs when the V0 level is tested, the oxygen index is ≥24%, and the relative dielectric constant is <2.7, which indicates that the non-crosslinked polyethylene material of the present invention has good flame retardant properties and dielectric properties. It can be seen from Examples 5, 6 and Example 4 that the non-crosslinked polyethylene injection molded sheets have good flame retardant properties, the flame retardant grades all reach the V0 level, no dripping occurs when the V0 level is tested, and the oxygen index is >25%; they have good dielectric properties, and the relative dielectric constant is <2.5; they also have good mechanical properties, with a tensile strength of ≥20Mpa, an elongation at break of >600%, and no cracking occurs when subjected to thermal shock at 110°C-150°C, which indicates that adding a toughening agent can improve the mechanical properties of the non-crosslinked polyethylene material. It can be seen from Example 4 and Comparative Example 1 that the number of modified POSS flame retardant 1 is too high, the flame retardant grade is V1, the flame retardant performance is not up to standard, the oxygen index is reduced, the dielectric properties are reduced, the relative dielectric constant is increased, and the elongation at break is reduced; It can be seen from Example 4 and Comparative Example 2 that when only the phosphorus-based flame retardant diethyl aluminum hypophosphite is used, the flame retardant grade is V2, there are drips, the flame retardant performance is not up to standard, the oxygen index is reduced, and the tensile strength, elongation at break and 150°C thermal shock are all reduced; It can be seen from Example 4 and Comparative Example 3 that only modified POSS flame retardant 1 is used as a flame retardant, and the flame retardant grade is V2, The flame retardant performance is not up to standard, the oxygen index is reduced, the dielectric properties are reduced, the relative dielectric constant is increased, and the elongation at break is reduced; It can be seen from Example 4 and Comparative Example 4 that the nitrogen-based flame retardant melamine urate (MCA) and the modified POSS flame retardant 1 are used together as flame retardants, the oxygen index is reduced, the dielectric properties are significantly reduced, and the relative dielectric constant is greatly increased; This shows that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist and the phosphorus-based flame retardant have a synergistic flame retardant effect, which reduces the dosage of various flame retardants while improving the flame retardant, dielectric properties and mechanical properties of non-cross-linked polyethylene materials.It can be seen from Example 4 and Comparative Example 5 that the modified POSS flame retardant 1 has improved anti-drip and oxygen index compared with the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, the relative dielectric constant is reduced, the dielectric properties are improved, there is no cracking at 150°C thermal shock, and the mechanical properties are improved; it can be seen from Example 4 and Comparative Example 6 that the modified POSS flame retardant 1 has improved flame retardancy, anti-drip, oxygen index, tensile strength and elongation at break compared with the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, the relative dielectric constant is reduced, and the dielectric properties are improved; it can be seen from Example 4 and Comparative Example 7 that the modified POSS flame retardant 1 has improved anti-drip and oxygen index compared with the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. , tensile strength and elongation at break are all improved, the relative dielectric constant is reduced, and the dielectric properties are improved; it can be seen from Example 4 and Comparative Example 8 that the flame retardant grade, anti-drip, oxygen index, tensile strength and elongation at break of modified POSS flame retardant 1 are improved, the relative dielectric constant is reduced, and the dielectric properties are improved; it can be seen from Example 4 and Comparative Example 9 that the flame retardant grade, anti-drip, oxygen index, tensile strength and elongation at break of modified POSS flame retardant 1 are improved, the relative dielectric constant is reduced, and the dielectric properties are improved, compared with modified POSS flame retardant 3, i.e., methyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; the anti-drip, oxygen index and tensile strength of modified POSS flame retardant 1 are improved, the relative dielectric constant is reduced, and the dielectric properties are improved, thereby illustrating that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists of the present invention have excellent flame retardant properties.
[0317] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A non-cross-linked polyethylene material, characterized in that: The raw materials of the non-cross-linked polyethylene material include, by weight: Polyethylene 50-90 parts, Phosphorus flame retardant 10-20 parts, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
2. The non-crosslinked polyethylene material according to claim 1, characterized in that The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
3. The non-crosslinked polyethylene material according to claim 1, characterized in that: The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows: 。 4. The non-crosslinked polyethylene material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:
1.
5. The non-crosslinked polyethylene material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
6. The non-crosslinked polyethylene material according to claim 1, characterized in that: The polyethylene includes at least one of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, and high-density polyethylene; And / or, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphorus oxide.
7. The non-crosslinked polyethylene material according to claim 1, characterized in that: The raw material of the non-cross-linked polyethylene material also includes at least one of a toughening agent and a compatibilizer. The raw materials are calculated by weight, and the toughening agent is 5-10 parts, and the compatibilizer is 3-8 parts.
8. The non-crosslinked polyethylene material according to claim 7, characterized in that: The toughening agent includes at least one of ethylene-octene copolymer, ethylene-propylene copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer.
9. The non-crosslinked polyethylene material according to claim 1, characterized in that: The raw materials of the non-cross-linked polyethylene material also include at least one of a lubricant, an antioxidant, and carbon black; wherein, in terms of weight, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, and the carbon black is 5-6 parts.
10. A method for preparing a non-crosslinked polyethylene material as claimed in claim 1, characterized in that: The following steps are involved: The raw materials, including polyethylene, phosphorus-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight portions to obtain an internal mixer material; The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the non-cross-linked polyethylene material.
11. The method for preparing a non-crosslinked polyethylene material according to claim 10, characterized in that: The raw materials also include at least one of a lubricant, an antioxidant, and carbon black; And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 150°C-180°C; And / or, the drying temperature is 80°C-90°C.